An attempt to reconstruct the late Saalian to Plenivistulian (MIS6-MIS3) natural lake environment from the "Parchliny 2014" section, central Poland. (20th February 2018) - Wachecka-Kotkowska, Lucyna; Krzyszkowski, Dariusz; Malkiewicz, Małgorzata; Mirosław-Grabowska, Joanna; Niska, Monika; Krzymińska, Jarmila; Myśkow, Elżbieta; Raczyk, Jerzy; Wieczorek, Dariusz; Stoiński, Andrzej; Rzodkiewicz, Monika
Abstract: The article presents the early results of research of sediments from a palaeolake in the Kleszczów Graben, central Poland. A total of 190 samples were collected and then ca 10–30 samples were botanically (diatoms, pollen and woody macrofossils), zoologically (Cladocera, Mollusca and Ostracoda) and geochemically (elemental content, carbon and nitrogen isotopes) tested. The results of muliproxy analysis of the Eemian (Aleksandrów Formation) and Vistulian (Weichselian; Piaski Formation) deposits helped to reconstruct the environmental changes occurring in the studied palaeolake. Palynological diagram of individual spectra "Parchliny 2014" was divided into five zones that represent local sets of pollen zones (E3−E7; PA-1−PA-5). This diagram, although incomplete, reveals the distinct Eemian features. Lithological, Cladocera and diatom analysis supported by geochemical studies indicate the existence of at least three main stages of the lake developed in the part of the basin. The lake originated from a post-Saalian melt-out kettle hole where the deposition of peats and organic, and mineral silts of different thicknesses to 10–12 m occurred (the first stage). In the second stage, initially existed a closed fairly deep Eemian lake under relatively warm conditions. The lower part of the section records an event of water body shallowing, consisting in its eutrophication, from oligotrophic to a lake of higher trophic status. Subsequently, in a cooler climate of Early Vistulian (Weichselian), the lake became shallower, and then open, flow and better oxygenated (flow-trough). Low frequency of ostracods and the absence of molluscs indicate slightly alkaline pH in the lower part of the water body, and neutral or slightly acidic pH in its upper part. At the bottom, the dominant organisms were diatoms, whereas toward the top, phytoplankton disappears and benthic taxa become predominant. Finally, in the third stage, in Plenivistulian, it was completely covered by mineral-organic and mineral sediments.